2009
DOI: 10.1016/j.bbamem.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Structure, membrane orientation, mechanism, and function of pexiganan — A highly potent antimicrobial peptide designed from magainin

Abstract: The growing problem of bacterial resistance to conventional antibiotic compounds and the need for new antibiotics has stimulated interest in the development of antimicrobial peptides (AMPs) as human therapeutics. Development of topically applied agents, such as pexiganan (also known as MSI-78, an analog of the naturally occurring magainin2, extracted from the skin of the African frog Xenopus laevis) has been the focus of pharmaceutical development largely because of the relative safety of topical therapy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
213
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(220 citation statements)
references
References 96 publications
3
213
0
Order By: Relevance
“…This has inspired other researchers to actually engineer disulfide bridges into natural monomeric and linear amphibian skin peptides to form such complexes. Bioassays indeed subsequently confirmed that synthetic heterodimers, such as between magainin 2 and PGLa, and between magainin and its analogue pexiganan (i.e., MSI-78), showed a greatly enhanced antimicrobial activity when compared to the original native (monomeric) peptides [21]. …”
mentioning
confidence: 68%
“…This has inspired other researchers to actually engineer disulfide bridges into natural monomeric and linear amphibian skin peptides to form such complexes. Bioassays indeed subsequently confirmed that synthetic heterodimers, such as between magainin 2 and PGLa, and between magainin and its analogue pexiganan (i.e., MSI-78), showed a greatly enhanced antimicrobial activity when compared to the original native (monomeric) peptides [21]. …”
mentioning
confidence: 68%
“…25,[32][33][34][35][36][37]. Therefore, synergistic bactericidal activity could result from the peptides having greater access to the cell membrane thanks to the cell wall-degrading abilities of lysostaphin.…”
Section: Discussionmentioning
confidence: 99%
“…They are very diverse in their sequences, length (generally short) and structures (some of them are linear while others are cyclic sometimes due to disulfide bridges, with a variety of secondary structures), but they adopt an amphipathic conformation that allows them to interact and disrupt selectively the negatively charged microbial membranes. No single mechanism can be defined for all AMPs, but despite these differences it can be concluded that they act mainly by binding to membranes and kill bacteria by disrupting membrane packing and organization, causing defects in the membrane with the consequent dissipation of transmembrane potential and leakage of important cellular contents [10][11][12]. In the case of PxB as well as cecropin and other AMPs, the proposed mechanism of action is based on the formation of periplasmic membrane contacts between outer and inner membranes.…”
Section: Introductionmentioning
confidence: 99%